Republic of Indonesia Financial Sector Assessment Program : Implementation of the IOSCO Objectives and Principles of Securities Regulation - World Bank (Washington, DC, 2017)
The law and related implementing regulations that constitute the regulatory framework affecting the capital markets in Indonesia are largely consistent with the International Organization of Securities Commissions (IOSCO) Objectives and Principles of Securities Regulation. Nevertheless this assessment finds that legislative reforms and other actions that are in the process of being implemented to clarify and expand the security regulator's authority and to cure certain self-acknowledged gaps should be accelerated. Further, the assessment concludes that attention must be paid to assure that implementation of the regulatory framework results in a system that reliably detects, deters, and sanctions securities violations and reliably identifies and prevents or mitigates prudential concerns. This may require legal reforms beyond those necessary to reform the specific capital markets law, as discussed more extensively by the separate legal assessor. How significant such further reform will be to enforcement effectiveness will depend in part on the manner in which regulatory enforcement powers and authorities are augmented and enhanced under the capital markets law revision. Capital markets operations are heavily dependent on legal certainty, and in particular reliable application of contract, company, insolvency, and other legal protections.